THE EFFECT OF EASE OF USE OF MOBILE BANKING APPLICATIONS ON USER SATISFACTION - Mardiansyah, Dandi; Zam Zam, Ari Mokti; Imron, Dimas Fawaid; Olek, Olek; Jayanti, Wanty Eka (Journal of Information Systems Management and Digital Business, 2025)
This study aims to analyse the effect of ease of use of mobile banking applications on user satisfaction. Using quantitative methods with data collection techniques through questionnaires distributed to 116 mobile banking user respondents. Data analysis using descriptive statistics and regression tests with the help of SPSS. The results showed that there is a positive and significant influence between the ease of use of mobile banking applications on user satisfaction, as evidenced by the t-count value (10.028) > t-table (1.988) with a significance of 0.000< 0.05. Ease of use of applications which include aspects of flexibility, clarity, and ease of operation contribute to increasing user satisfaction. This finding indicates that the easier it is to use the mobile banking application, the higher the level of user satisfaction. Keywords: ease of use, mobile banking, user satisfaction.